Economic security management in the context of national entrepreneurship development using artificial intelligence tools - Pavlova, Olena Mykolaivna; Pavlov, Kostiantyn Volodymyrovych; Totska, Olesia Leontiivna; Mahdysiuk, Denys Eduardovych (My University, 2025)
Economic security is a critical factor in ensuring enterprises’ stability, competitiveness, and contribution to Ukraine’s national economic development. Amid globalisation, digitalisation, and rising cyber threats, enterprises face complex challenges that require innovative management approaches. Artificial Intelligence (AI) technologies offer new opportunities for automating business processes, predicting risks, and responding swiftly to threats, enhancing the economic security of individual enterprises and supporting national economic growth, job creation, and innovation initiatives. In Ukraine’s wartime and post-war challenges, AI is a strategically vital tool for ensuring business resilience and supporting national priorities such as digital transformation and economic recovery. This article aims to analyze directions for improving economic security management in enterprises that utilize AI technologies, focusing on their contribution to Ukraine’s national development. The study encompasses defining economic security and its role in the national economy, analyzing AI’s potential in economic security management, evaluating the challenges and prospects of AI implementation in Ukrainian enterprises, and developing recommendations for leveraging AI in national development.The researchis based on scientific publications, analytical reports, and statistical data from recent studies. The methodological framework includes a systemic approach, integrating economic security theories, AI applications, and national development perspectives. The study employs interdisciplinary analysis to address the challenges of wartime and post-war economic conditions in Ukraine, drawing on theoretical works and practical case studies to evaluate the role of AI in economic security management. The study identifies economic security as a multifaceted condition encompassing financial stability, information security, risk management, and innovation sustainability, contributing to enterprise competitiveness and national economic growth. Key findings include that AI enables real-time data analysis, anomaly detection, and process automation, enhancing enterprises’ ability to counter financial and cyber threats; AI improves risk forecasting accuracy by 20–30% compared to traditional methods, supporting financial stability and economic recovery in Ukraine’s wartime context. Challenges to AI adoption include high costs, limited access to quality data, and ethical considerations, particularly for small and medium-sized enterprises. Recommendations include developing accessible AI solutions, establishing legal frameworks for AI regulation, improving data processing methods, and promoting state-supported digital transformation programs to integrate AI into business processes, thereby strengthening economic security and supporting national development goals.
Економічна безпека є критично важливим фактором забезпе-чення стабільності, конкурентоспроможності та внеску підприємств у розвиток національної економіки України. В умовах глобалізації, цифровізації та зростання кіберзагроз підприємства стикаються зі складними викликами, що вимагають інноваційних підходів до управління. Технології штучного інтелекту (ШІ) відкривають нові можливості для автоматизації бізнес-процесів, прогнозування ризиків та швидкого реагування на загрози, тим самим не тільки підвищуючи економічну безпеку окремих підприємств, але й сприяючи національному економічному зростанню, створенню робочих місць та інноваційним ініціативам. У контексті воєнних та післявоєнних викликів України ШІ є стратегічно важливим інструментом для забезпечення стійкості бізнесу та підтримки національних пріоритетів, таких як цифрова трансформація та економічне відновлення. Ця стаття має на меті проаналізувати напрями вдосконалення управління економічною безпекою на підприємствах з використанням технологій ШІ, з акцентом на їхньому внеску в національний розвиток України. Дослідження охоплюєвизначення економічної безпеки та її ролі в національній економіці, аналіз потенціалу ШІ в управлінні економічною безпекою, оцінку викликів і перспектив упровадження ШІ на українських підприємствах, а також розробку рекомендацій щодо використання ШІ в контексті національного розвитку. Дослідження базується на наукових публікаціях, аналітичних звітах і статистичних даних останніх досліджень. Методологічна база включає системний підхід, що інтегрує теорії економічної безпеки, застосування ШІ та перспективи національного розвитку. У дослідженні використовується міждисциплінарний аналіз для вирішення викликів воєнного та післявоєнного економічного стану в Україні, спираючись на теоретичні роботи та практичні кейси для оцінки ролі ШІ в управлінні економічною безпекою. Дослідження визначає економічну безпеку як багатогранний стан, що охоплює фінансову стабільність, інформаційну безпеку, управління ризиками та стійкість інновацій, які сприяють конкурентоспроможності підприємств та національному економічному зростанню. Основні висновки: ШІ дозволяє здійснювати аналіз даних у реальному часі, виявляти аномалії й автоматизувати процеси, підвищуючи здатність підприємств протистояти фінансовим і кіберзагрозам; ШІ підвищує точність прогнозування ризиків на 20–30% порівняно з традиційними методами, підтримуючи фінансову стабільність та економічне відновлення в умовах війни в Україні. Виклики для впровадження ШІ включають високі витрати, обмежений доступ до якісних даних та етичні міркування, особливо для малих і середніх підприємств. Рекомендації включають розробку доступних рішень ШІ, створення правових рамок для регулювання ШІ, вдосконалення методів обробки даних і просування підтримуваних державою програм цифрової трансформації для інтеграції ШІ в бізнес-процеси, тим самим зміцнюючи економічну безпеку та підтримуючи національні цілі розвитку.
Keywords: economic security; artificial intelligence,; ational development; digital transformation,; cybersecurity; isk management; innovation sustainability; wartime economy; 330.341.1:004.8:338.27